Penatalaksanaan Degenerasi Makula Terkait Usia (AMD) dengan Suplemen AREDS2: Tinjauan Pustaka - Guna Dharma, Andhika (PT Kalbe Farma Tbk., 2026)
Age-related macular degeneration (AMD) is a degenerative disease of the macula that is the leading cause of blindness in the over-50 population. AMD is divided into non-exudative (dry) and exudative (wet) types, with the dry type accounting for 90% of cases. The main clinical features of dry AMD include drusen, hyperpigmentation or hypopigmentation of the retinal pigment epithelium (RPE), and geographic atrophy in advanced stages. Management of dry AMD focuses on preventing disease progression, one of which is through antioxidant supplementation based on the Age-Related Eye Disease Study (AREDS) and AREDS2 studies. AREDS2 supplementation, which contains vitamin C, E, zinc, copper, lutein and zeaxanthin, was shown to slow the progression of dry AMD by 55% over three years in cases of geographic atrophy beyond the fovea. In addition to nutritional supplementation, appropriate management includes early diagnosis, regular ophthalmic follow-up, and modification of risk factors such as smoking cessation and maintaining a healthy lifestyle to reduce the risk of disease progression. Early recognition and timely intervention are essential to preserve visual function and improve patients’ quality of life. This review aims to outline the pathophysiology, risk factors and management of AMD with an emphasis on the role of AREDS2 supplementation in preventing disease progression.